An effective HPLC‐based approach for the evaluation of the content of total phenolic compounds transferred from olives to virgin olive oil during the olive milling process. (20th February 2018) - Cecchi, Lorenzo; Migliorini, Marzia; Zanoni, Bruno; Breschi, Carlotta; Mulinacci, Nadia
Abstract: BACKGROUND: Several studies demonstrate a strong interest in learning more about phenolic transfer during oil extraction, with the main goal of increasing the phenolic concentration in olive oils. We aimed to propose and apply a new methodological approach for evaluating phenolic transfer from olives into oil during milling, based on the quantification of phenolic content in whole lyophilized fruits and the corresponding oils and considering the oil extraction yields. RESULTS: We investigated the phenols transferred into the oil during olive milling in continuous extraction systems in Tuscany. In 2012, oils were extracted from cultivar Frantoio by a two‐phase extraction system; in 2016, oils were extracted from cultivars Leccio del Corno and Arbequina by a three‐phase extraction system. Results highlighted very low percentages of extracted phenols: up to 0.40% by the two‐phase system and up to 0.19% by the three‐phase system (0.08% for cultivar Arbequina and 0.19% for cultivar Leccio del Corno). CONCLUSION: The usefulness of a simple and effective methodological approach for evaluating the extracted phenols was highlighted. Values of extracted phenols were up to 25 times lower than previous literature data. The proposed approach is applicable in all types of milling processes. © 2017 Society of Chemical Industry